Analysis of The Level of 21st Century Skills in Productive Teachers at SMK Negeri 2 Padang Panjang - Oktavia, Sri; Alfiriani, Adlia; Samudra, Ami Angggraini (Journal of Educational Sciences, 2024)
In this 21st century, there are special skills that must be mastered by teachers, especially productive teachers, namely 21st century skills. This study aims to determine the level of 21st century skills possessed by productive teachers at SMK Negeri 2 Padang Panjang. The research method used is quantitative with survey research design. The study population was all teachers at SMK Negeri 2 Padang Panjang, and the sample was taken using purposive sampling technique so that the number of respondents was 26 people. Data analysis was carried out descriptively using index numbers. The research results of this study are the 21st century skill level of productive teachers at SMK Negeri 2 Padang Panjang is classified as in the high category, as evidenced by the high index scores obtained for life and career skills, learning and innovation skills, as well as information, media and technology skills. Based on the research results, productive teachers at SMK Negeri 2 Padang Panjang have a good understanding of the importance of applying 21st century skills in the learning process, as evidenced by the high index value obtained. However, there are several indicators of 21st century skills that are still below the average index value.